The Relationship Between Household Characteristics and Beef Consumption in Batang Toru District, South Tapanuli Regency - R. Nasution; A. H. Daulay; M. Tafsin (Talenta Publisher, 2021)
Animal protein one of which is obtained by consuming meat. This study aims to determine the social and economic characteristic of household and to analyze the factors that influence household beef consumtion in Batang Toru District. The analytical method used is descriptive analysis by directly observing the social and economic conditions of the household, then using a questionnaire to obtain data on the socio-economic conditions of the household. The results of the study indicate that beef consumers in Batang Toru district have differents socio-economic charasterictics, both in terms of education, age, number of family members and income. The socio-economic charasteristics of beef consumers, namely education, age, number of family members and income, have a significant effect Â on the amount of beef consumption. While the variable number of family members does not significantly affect Â on the amount of beef consumtion.